Edukasi Orang Tua Terkait Tumbuh Kembang Balita Fisioterapi Komunitas Di Posyandu Menur IX Makamhaji - Adnan Faris Naufal; Wahyu Tri Sudaryanto; Oktaviani Fitriyah; Anggun Pramudya Putri; M Irfan Alhady (Jurnal Pengabdian Masyarakat, 2023)
Children are the hope of the next generation for parents, so children need to be raised and cared for properly and also pay attention to their growth and development, good growth and development and according to their age will show optimal results. Growth and development problems in toddlers are caused by reduced stimulation given to toddlers. This can be caused by the lack of knowledge of parents of toddlers about adequate stimulation according to the stage of toddler growth and development. Therefore, this study aims to provide education to parents regarding the importance of knowledge on growth and development in toddlers. The evaluation is carried out with pretest and postest filled by parents of toddlers.